Differences in Problem Solving Ability and Confidence of Students Who Get Learning Using PBL and GI Models - Khairin Nazmi AR; Asmin Asmin; Dian Armanto (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2022)
This study aims to determine: (1) statistically test and analyze the problem-solving abilities of students taught by the Problem Based Learning model or not higher than students taught by the Group Investigation learning model; (2) statistically testing and analyzing the self-confidence of students who are taught by the Problem Based Learning model are higher or not than students who are taught by the Group Investigation learning model; (3) the interaction between learning models (PBL and GI) with early mathematical abilities (KAM) on students' problem-solving abilities; (4) the interaction between learning models (PBL and GI) with early mathematical abilities (KAM) on students' self-confidence abilities. This research is quasi-experimental. The population in this study consisted of all students of class X MA Ponpes Darul Quran totaling 210 students in the 2021/2022 academic year, taking samples of two classes totaling 70 students using the cluster random sampling technique. Data analysis was performed using a two-way analysis of variance (ANOVA). The results of this study indicate that: (1) The problem-solving abilities of students who are taught problem-based learning are higher than students who are taught by group investigation, and (2) the Self-Confidence of students who are taught problem-based learning is higher than students who are taught by group investigation. , (3) there is no interaction between the learning model and KAM on students' problem-solving abilities, and (4) there is no interaction between the learning model and KAM on students' self-confidence abilities.